Settlement of Sharia Economic Disputes through the Al-Shulhu Approach: A Case Study of Default in Murabahah Contracts in Indonesia - Muhammad Said; Islamul Haq; Zulfahmi AR (Qiyam Islamic Studies Center Foundation, 2026)
This study aims to examine the effectiveness of the al-shulhu approach in resolving Islamic economic disputes, particularly in cases of breach of murabahah contracts in Indonesia. Employing a qualitative approach with a library research design, this study collects data from academic journals, books, and regulations such as DSN-MUI fatwas through qualitative content analysis. Source selection was based on criteria of relevance to the topic, recency of publication (focusing on the 2020–2025 range). The findings indicate that al-shulhu, rooted in the principle of sulh in the Qur’an (Surah An-Nisa: 128), is an effective dispute resolution mechanism as it emphasizes justice (al-‘adl), honesty (as-sidq), and mutual consent (ridhā). This approach enables solutions such as financing restructuring or penalty reductions without violating sharia principles, while maintaining social harmony between Islamic banks and clients. However, the application of al-shulhu faces challenges, including the lack of a clear legal framework, inconsistent implementation across institutions, and a shortage of competent mediators with expertise in Islamic law. This study contributes to academic discourse by bridging classical Islamic legal theory with modern dispute resolution practices and provides practical recommendations for Islamic financial institutions and regulators, such as OJK and DSN-MUI, to integrate al-shulhu into the national legal system through clear regulations and mediator training. The study recommends further empirical research to enhance understanding of al-shulhu’s application in religious courts and Islamic financial institutions.